An unusual case of coexistence of psoriasis and lichen planus - Kondras, Katarzyna; Omulecki, Anastazy (Dermatology Review/Przegląd Dermatologiczny, 2012)
Introduction . Psoriasis and lichen planus are common skin diseases, but their coexistence is rare. In spite of some similarities there are many distinct characteristics such as clinical and histopathological features, triggering factors and immunological processes. Objective . To present a case with clinical and histopathological features of psoriasis and lichen planus. Case report . We present a rare case of psoriasis and lichen planus coexistence in a 66-year old man. He had a 15-year history of lichen planus-like and eczematous lesions, then psoriasis-like lesions were also observed. The currently taken skin biopsy revealed histopathological features of both diseases: psoriasis and lichen planus. Conclusions . Our case indicates that detailed clinical and histopathological examination, especially in cases with unusual course of skin disease, resembling psoriasis and/or lichen planus, is necessary.